Minimally invasive plate osteosynthesis for humeral shaft fracture: a reproducible technique with the assistance of an external fixator - Lee H.-J. (2014)
Background: Minimally invasive plate osteosynthesis (MIPO) has become a popular option for treatment of humeral shaft fractures. However, indirect reduction might risk unpromising results, with mal-alignment/mal-union or nonunion. The purpose of this study was to describe a reproducible MIPO technique that used an external fixator during the procedure as a tool for reduction and maintenance, and to assess the outcomes in patients with humeral shaft fracture. Methods: Of 31 consecutive cases of humeral shaft fracture in 30 patients, 29 were included in this study. There were seven simple (type A) and 22 comminuted (type B or C) fractures. After the insertion of one Schanz pin on each proximal and distal humerus, a provisional reduction was achieved by connecting the pins with a monolateral external fixator. The MIPO procedure was then performed over the anterior aspect of the humerus. To evaluate the efficacy of the provisional reduction by external fixator, coronal and sagittal alignments were assessed. We also assessed bony and functional results, including complications, from this technique. Results: There was no case of mal-union >10, and mean angulation was 1.3 (range 0 -9) in the coronal plane and 1.2 (range 0 -8) in the sagittal plane. Twenty-eight of 29 fractures were united, including three delayed unions, with a mean union time of 19.1 weeks (range 12.3-38.4 weeks) and a mean follow-up of 20.8 months (range 13.5-31.0 months). There was one hypertrophic nonunion that healed after fixing with two additional screws. Except one patient with associated injury in the elbow, all patients recovered to pre-injury joint motion. There were two cases of postoperative radial nerve palsy that both recovered completely. We attributed them to manipulation, and not to the Schanz pins or plate fixation. Conclusions: Surgical treatment of humeral shaft fractures with external fixator-assisted reduction and MIPO resulted in excellent reductions and high union rates. Level of Evidence: IV © 2013 Springer-Verlag Berlin Heidelberg.